Work The Influence of Resilience And Work-Family Conflict on The Stress of Working Mothers in Long-Distance Marriages - Mardliyah, Afifah; Hayuputri, Frida Medina; Sovitriana, Rilla (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
Women are afforded the same opportunities as men in the workplace; however, they are confronted with particular challenges, one of which is the conflict between work and family demands, which is commonly referred to as work-family conflict (WFC). WFC is regarded as a significant source of stress, particularly for women in long-distance marriages. The physical absence of a spouse, coupled with the emotional challenges of a physical and emotional distance, can precipitate an increase in stress levels. It is hypothesised that resilience is a supportive factor in the management of stress. This study examines the impact of resilience and work-family conflict (WFC) on stress levels among working mothers. The research employed purposive sampling technique with a non-probability sampling approach, involving 354 respondents who were working mothers residing in the Indonesian provinces of Sumatra and Java. The measurement tools employed were Connor-Davidson Resilience Scale (CD-RISC), Work-Family Conflict Scale (WFCS), and Perceived Stress Scale (PSS-10), with data analysis conducted using JASP 0.19.1.0 for Windows. The findings of this study indicate a significant influence of resilience and WFC on stress levels among working mothers in long-distance marriages. These results provide scientific evidence that resilience plays an essential role in mitigating the effects of WFC on stress.